THE EFFECT OF CASTOR OIL ON INITIATING LABOR IN 40-42 WEEKS PREGNANCY - S Pirdadeh Beiranvand (Babol University of Medical Sciences, 2007)
BACKGROUND AND OBJECTIVE: At present, there are different methods of induction (mechanical, surgical and pharmaceutical) to prevent prolonged pregnancy. Each one of these methods has several maternal and fetal complications. Castor oil is among those herbal preparations which are used widely for induction of labor, but only a few studies have been done to evaluate its efficacy and safety. The aim of this study was to determine the effects of castor oil on initiating labor in term pregnant women who referred to Imam Reza maternity hospital and special clinic and also Pastor maternity hospital in Mashhad in 2003.METHODS: This randomized control clinical trial study was done on 47 pregnant women (24 patients in castor oil group and 23 cases in control group) with the gestational age of 40-42 weeks without any evidence of regular uterine contractions. Their Bishop score was 4 or less and there weren’t any clinical or obstetrical complications. At first, we selected our cases according to the objective and then we divided them into castor oil and control groups. We gave 60cc of castor oil to the trial group and there wasn’t any intervention in the control group. We followed up the labor progression for 24 hours in both groups. To gather information we used forms based on interview, observation and physical examination and also we used a form to record the fetal movements. FINDINGS: There was a significant increase in labor initiation ratio in the castor oil group (54.2%) compare with the control group (4.3%) (p<0.001). Also the mean Bishop score in the castor oil group increased from 2.50± 1.29(at first) to 6.79± 3.20 (at the end) (p< 0.001).CONCLUSION: The probability of labor initiation increases during the first 24 hours after using castor oil but more studies are recommended to improve its efficacy and safety.